Rationale for a reverse tapered body shift implant for immediate placement. Issue 12 (December 2020) - Christiaens, V.; Pitman, J.; Glibert, M.; Hommez, G.; Atashkadeh, M.; De Bruyn, H.
Abstract: Immediate implant placement holds considerable value, yet primary implant stability is often a critical factor. The aim of this study was to evaluate the stability, volumetric viability, and buccal gap size of reverse tapered body shift (RTBS) implants after immediate placement. Peak insertion torque measurements of two RTBS designs (apical 40% vs. apical 50%), relative to conventionally tapered implants, were assessed in simulated extraction sockets prepared in synthetic bone blocks. Additionally, the proximity of the RTBS implants to neighbouring teeth and anatomical structures, and the buccal gap distance were evaluated in human cadavers. The mean (± standard deviation) insertion torque was 12.00 ± 1.40 Ncm for the conventionally tapered implants ( n = 50), 35.36 ± 2.74 Ncm ( n = 50) for RTBS-1, and 48.20 ± 2.90 Ncm ( n = 50) for RTBS-2; the difference between designs was statistically significant ( P < 0.01). In total, 40 RTBS implants (20 per design) were placed in six cadaveric premaxillae. Only one locus was inappropriate for both RTBS implant designs, due to the proximity of neighbouring teeth. The average buccal gap for both implant designs was 2.8 mm ( P = 0.104). The improved primary stability and increased buccal gap size with RTBS implants may enhance the feasibility of immediate placement. The study findings should be further validated in clinical trials.